RENAL EVENTS AMONG WOMEN TREATED WITH TENOFOVIR/EMTRICITABINE IN COMBINATION WITH EITHER LOPINAVIR/RITONAVIR OR NEVIRAPINE: ANALYSIS FROM THE AIDS CLINICAL TRIAL GROUP (ACTG) A5208 TRIAL - MWAFONGO, Albert (2014)
OBJECTIVES: Tenofovir disoproxil fumarate (TDF) has been associated with renal insufficiency. Co-administration with boosted protease inhibitors (PIs), which increases its exposure, may further increase the risk of renal insufficiency. METHODS: We compared the incidence of renal events among women taking TDF co-administered with lopinavir/ritonavir (LPV/r) versus those co-administering TDF with nevirapine (NVP). Renal events were defined as a confirmed drop in creatinine clearance associated with a serum creatinine grade 2 or higher, or that leading to treatment modification. RESULTS: Overall, 741 HIV-infected women were enrolled into the study. Of these, 24 (3.2%) had reportable renal events (18 in LPV/r arm, 6 in NVP arm). In multivariate analysis, renal events were significantly associated with the LPV/r arm (odds ratio [OR]=3.12, 95% confidence interval [CI] 1.21, 8.05]; p=0.019), baseline HIV-1 RNA (OR=2.65, 95% CI: 1.23, 5.69 per 1 log(10) copies/mL higher; p=0.013) and baseline creatinine clearance (OR=0.83, 95% CI 0.70–0.98 per 10 mL/min higher; p=0.030). In multivariate analysis evaluating renal events requiring treatment modification, only baseline HIV-1 RNA and creatinine clearance were significantly associated (OR=4.41, 95% CI 1.65, 11.78 per 1 log(10) copies/mL higher; p= 0.003 and OR=0.80, 95% CI 0.64, 0.99 per 10 mL/min higher; p= 0.040, respectively). CONCLUSION: The rates of renal events were relatively low in the two treatment arms. However, patients taking TDF co-administered with LPV/r had significantly more renal events compared to those co-administered with NVP. Furthermore, higher baseline HIV RNA and lower creatinine clearance were associated with the development of renal insufficiency requiring treatment modification.